2021
DOI: 10.3390/ijerph18084110
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Affect and Personality as Predictors of Engagement in Nursing Professionals

Abstract: Background: It seems that personality traits affect engagement and the quality of professional life, which is mediated by the emotional and affective states of nursing personnel. Therefore, the objectives of this study were to analyze the relationships between the components of empathy, affect, personality, and engagement, find personality profiles, identify the variables with the most explanatory value, and analyze the mediating role of the variables susceptible to intervention in the relationship between per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The results show that the Big Five-type general personality traits had some predictive capacity over work engagement (Bakker et al, 2012;Bhatti et al, 2018;Hau & Bing, 2018;Martos Martínez et al, 2021;Zaidi et al, 2013), although that capacity improved notably when specific traits of enterprising personality were also used. These results are consistent with previous studies (Leutner et al, 2014;Postigo et al, 2021;Rauch & Frese, 2007) that showed how the evaluation of more specific behaviors more accurately expressed a specific behavioral description and could predict criteria that were closely linked to that description (John et al, 2008;Soto & John, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The results show that the Big Five-type general personality traits had some predictive capacity over work engagement (Bakker et al, 2012;Bhatti et al, 2018;Hau & Bing, 2018;Martos Martínez et al, 2021;Zaidi et al, 2013), although that capacity improved notably when specific traits of enterprising personality were also used. These results are consistent with previous studies (Leutner et al, 2014;Postigo et al, 2021;Rauch & Frese, 2007) that showed how the evaluation of more specific behaviors more accurately expressed a specific behavioral description and could predict criteria that were closely linked to that description (John et al, 2008;Soto & John, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Ramírez-García et al ( 2019) considered two factors related to worker happiness, one which included a worker's personal factors, and the other which was about aspects of work environment. Personal happiness slightly increased the prediction of work engagement, because there are certain aspects related to happiness and wellbeing that are not only explained by personality and which lead the employee to be engaged with their work (Fisher, 2010;Martos-Martínez et al, 2021;Salas-Vallina et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations